2005
DOI: 10.7202/705375ar
|View full text |Cite
|
Sign up to set email alerts
|

Signature isotopique et chimique des précipitations (pluies et pluviolessivats) en Guyane française

Abstract: We also noted that the integrated value of S 18 0 for throughfall was slightly more concentrated than the content of rain. In the absence of evaporation (the isotopic composition of the throughfall corresponded to the local meteoric Une), this enrichment suggests that direct rain mixed with older water that was stored in the canopy and had a différent isotopic composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Thus, it appears that no Cl is released from litter during the storm event studied. Chloride is first of all supplied by the rain, so its concentration classically increases between rainwater and throughfall (Brouwer, 1996;Grimaldi and Pedro, 1996;Cornu et al, 1998), a feature also observed in the stormflow event studied by Millet et al (1999). This increase is due to the washing out of dry deposits and salts left on the leaves by the evaporation of rain between downpours.…”
Section: Chloridementioning
confidence: 87%
See 2 more Smart Citations
“…Thus, it appears that no Cl is released from litter during the storm event studied. Chloride is first of all supplied by the rain, so its concentration classically increases between rainwater and throughfall (Brouwer, 1996;Grimaldi and Pedro, 1996;Cornu et al, 1998), a feature also observed in the stormflow event studied by Millet et al (1999). This increase is due to the washing out of dry deposits and salts left on the leaves by the evaporation of rain between downpours.…”
Section: Chloridementioning
confidence: 87%
“…For the storm-flow event studied, Millet et al (1999) showed that H 4 SiO 4 and Al are released during the passage of rain through the canopy. Nevertheless, the concentrations remain low in the throughfall, being lower than 5 µM for H 4 SiO 4 and up to 30 µM for Al (Figure 4).…”
Section: Silica and Aluminiummentioning
confidence: 99%
See 1 more Smart Citation
“…The initial excess deuterium in rainfall deviates from 10 in relation to the evaporation conditions at the origin of the vapor and the influence of continental vapor [17][18][19]. This probably reflects the recycling of air masses by water vapor from water body evaporation and soil evapotranspiration [2,20,21].…”
Section: Discussionmentioning
confidence: 99%